Establishment and Application of a Monitoring Strategy for Living Modified Cotton in Natural Environments in South Korea - Hye Song Lim; Il Ryong Kim; Sunghyeon Lee; Wonkyun Choi; A-Mi Yoon; Jung Ro Lee (Applied Sciences, 2021)
Cotton (Gossypium hirsutum L.) is grown worldwide for its natural hollow fibers and is used as cattle feed. Living modified (LM) cotton is not cultivated in South Korea and must be imported for food, feed, and processing. From 2009 to 2013, the Ministry of Environment (MOE) and the National Institute of Ecology (NIE) conducted a natural environment monitoring and post-management initiative for living modified organisms (LMOs) in some areas to reduce the likelihood of harmful effects caused by unintentionally discharged LMOs during transportation and use. In this study, we adopted a new strategy to identify unintentionally released LM cotton plants nationwide from 2014 to 2018. A total of 451 suspicious cotton samples were collected from 3921 survey sites. Among them, we identified 255 LM cotton plants, of which approximately 72.2% had transgenic herbicide and insecticide traits. The majority of the samples were collected from the roadside along transportation routes and from stockbreeding farms. This study establishes an LMO safety management system to efficiently maintain conservation efforts in South Korea. Our findings suggest that these efforts may play a key role in safely transporting, using, and managing approved LMOs, as well as in regulating unintentionally released LMOs, in order to preserve the natural ecosystem of South Korea.